Application of the Jibril Method to Improving Fashahatul Qiro'ah at al-Qur'an Education Park - BZ, Zakiyah; Sofi, Muhammad; Thelma, Chanda Chansa (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2025)
This study analyzes the implementation of the Jibril Method in improving fashahatul qiro'ah (fluency in reading the Qur’an) at Riyadus Sholihin Qur’anic Education Park in Krejengan, Probolinggo. The Jibril Method is an innovative approach that emphasizes interactive learning through repeated practice, alternating reading between the teacher and students, and direct teacher guidance. This research employs a qualitative method with a descriptive approach. Data were collected through observations, in-depth interviews with teachers and students, and analysis of learning documents. The results indicate that the application of the Jibril Method significantly enhances students’ fashahatul qiro'ah, as evidenced by improvements in letter pronunciation, application of tajwid rules, and reading fluency. The method’s success is supported by active teacher involvement, structured repetition, and high student motivation. However, challenges such as differences in students’ initial abilities and limited learning time were also identified. With proper time management and intensive guidance, the Jibril Method proves to be effective in enhancing Qur’anic reading skills. These findings are expected to serve as a reference for other Qur’anic educational institutions in optimizing their learning methods